The role of seafood sustainability knowledge in seafood purchase decisions. Issue 10 (7th October 2019) - Lawley, Meredith; Craig, Jane F.; Dean, David; Birch, Dawn
Abstract : Purpose: The purpose of this paper is to explore consumer knowledge of seafood sustainability and how that knowledge influences the purchase of seafood products. Design/methodology/approach: Using an online survey ( n =1, 319), the authors investigated Australian consumer knowledge of seafood sustainability and the drivers of purchase choice. Objective knowledge categories were developed through the qualitative analysis of unprompted, open-ended responses and compared with other surveyed measures of objective knowledge. The relationship between these knowledge categories and the importance of sustainability in the purchase decision was tested. Findings: A significant group of consumers either had no knowledge of seafood sustainability (17.8 per cent) or gave an incorrect response (15.5 per cent), while 25.1 per cent demonstrated simple and 41.6 per cent complex knowledge. Further, the knowledge was positively related to importance of sustainability when making purchase decisions. Sustainability moved from the lowest ranked attribute for the no knowledge group to the highest ranked attribute for the complex knowledge group. Research limitations/implications: The results show that the consumer knowledge about sustainable seafood cannot be assumed and that the level of sustainability knowledge influences the importance of sustainability in the purchase decision. Practical implications: The results suggest that information-based strategies based on a universally shared definition of sustainability in the seafood industry designed to drive sustainable consumer behaviour for seafood must take the account of consumer knowledge. Originality/value: This paper identifies and provides a classification framework for levels of consumer knowledge about sustainable seafood and demonstrates a positive relationship between knowledge and the importance of sustainability in consumer decisions with regard to purchasing seafood.